ANALISIS VARIANS DAN PERTUMBUHAN BELANJA DAERAH PADA PEMERINTAH KOTA MAGELANG TAHUN 2018-2021 - Afri Liyani, Yolanda; Tiska Luthfita Desanti Putri Suharto, Vara; Wira Bharata3, Risma (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
To effectively manage the Regional Expenditure Budget, a control system is needed that takes into account the factors influencing budget preparation. The objective of allocating the Regional Expenditure Budget is to achieve a balance between expenditures and cash receipts. This study aims to evaluate the variance and growth of regional expenditure. The research method used is descriptive analysis, utilizing primary data obtained from the Magelang City Government. The results of the research conducted on the Office of Financial Management and Government Property of Magelang City demonstrated that the financial performance of the Magelang City Government can be assessed through variance analysis of expenditures. The average value of the difference (variance) is 26.7, while the average utilization or absorption of the expenditure budget is 73.14%. Based on these calculations, it can be concluded that the government has effectively accomplished budget planning and efforts to utilize the budget. Budget utilization of more than 90% indicates efficient use of the budget, while utilization of less than 90% suggests a lack of budget planning.